Advertising and creativity in award ceremonies: the challenge of transparent evaluation - Tur-Viñes, Victoria; Castelló-Martínez, Araceli; Ramos-Serrano, Marina; Zacipa-Infante, Ingrid (Creativity Studies, 2024)
Award ceremonies value and highlight the best pieces of communication, reflecting the innovative trends of advertising practice, and are also on the rise as places for meeting and exchanging experiences, points of reflection on the challenges facing the industry and events to showcase the high value of the industry. The aim of this study is to evaluate the methodology of advertising festivals and identify the criteria for their operation. A content analysis of the official websites of 85 international award ceremonies with 20 indicators was carried out. The results show the non-specialized, general nature of most of the annual events. Five major award category types are identified: media and actions, digital, differential feature of the endeavour, resources used and results obtained. The jury selection criteria are only made public for one in ten award ceremonies, while the criteria for the assessment of the pieces are not known for 40% of the award ceremonies. This study has theoretical–practical implications, and expands upon previous knowledge regarding award, the selection of people and pieces, and the criteria for both. It concludes by underlining transparency as a potential area for improvement.